Theatre as alternative historical narrative : a study of three plays : "Ubu and the Truth Commission", "Copenhagen" and "Ghetto" - Faasen, Cornelia (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MDram (Drama))--University of Stellenbosch, 2009.